Tax Aggressiveness: The Role of Capital Intensity and Inventory Intensity with Leverage as Intervening - Elin Marlina; Agus Ismaya Hasanudin; Windu Mulyasari (PT. EQUATOR SINAR AKADEMIA, 2022)
This Research Aims To Know The Effect Of Capital Intensity And Inventory Intensity On Tax Aggressiveness And To Know The Role Of Leverage In Mediating Capital Intensity And Inventory Intensity To Tax Aggressiveness In The Mining Industry In Indonesia. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) from 2016-2020. The sample used in this study was selected by purposive sampling. The sample of companies that were successfully obtained in this study was 45 companies. The Source of data used in this study is secondary data with a purposive sampling method. The data analysis technique used is with the help of the SPSS Version 20.00 Application Program for WindowsThe results showed that Capital Intensity has a positive effect on Tax Aggressiveness, Inventory intensity has a positive effect on Tax Aggressiveness, Leverage is not able to mediate Capital Intensity on Tax Aggressiveness, Leverage is not able to mediate Inventory Intensity on Tax Aggressiveness and Leverage has a positive effect on Tax Aggressiveness.